Career succession planning and its role in improving the professional competencies of human resources in educational institutions - Moawad, Huda Salem (Journal of Economic, Administrative and Legal Sciences, 2024)
The concept and system of career succession planning is considered one of the most important concepts and current requirements to keep pace with the strategic plans and what is built on them in the future in terms of goals and visions. It is also one of the requirements of Vision 2030 adopted by the Kingdom of Saudi Arabia to create its vibrant economies and societies, and there is no doubt that career succession planning is one of the important topics for all institutions in their various fields and activities. By reviewing the literature and previous studies, the researcher noticed the lack of theoretical studies and its shortage in addressing the issue of career succession and its role in improving and enhancing professional competencies, so the study came in this way. This study aimed at: 1- Formulating a proposal for career succession planning and a course in improving professional competencies and improving them by human resources, by answering the main question(problem study) : What is the impact of career succession planning on improving and enhancing professional competencies for human resources in educational institutions. Analyzing the general framework of the concept of job succession and the dimensions of that concept,  The relationship of succession planning in creating second-row leaders and the role of human resources management in implementing succession plans. The analytical descriptive approach was used as a main tool for the research through a sample of (520) employees from the Yanbu Education Department. It also relied on a questionnaire to survey the opinion and measure the results consisting of four main axes. The data was analyzed using the statistical programs prepared for that to come out with the results of the study. The study resulted in results, the most important of which are: Employees' realization in the Yanbu Education Department of the importance of career succession planning, its targeting for the future, and its contribution and role in perpetuating the educational and institutional work. The employees of the educational institution see the need to create a second row of leaders who will assume leadership positions in the future.
Keywords: career succession planning; professional competencies; human resources